Scientific interpretation of the Fatima events - Kulczyk, Wojciech K. (2019)
The events and apparitions that took place in Fatima are very unusual as they are supported by extensive written evidence. This evidence was made available to the public thanks to the publication of a book1 by the late Fina d’Armada. This book provides comprehensive information about the events through the eyes of seers and witnesses. In such cases everything depends on the trustworthiness of witnesses and people gathering information. After reading the book I believe that the children were trustworthy witnesses especially as they were interviewed immediately after the events. The statements of witnesses describing the display in the sky on 13th October do not differ much and this provides some confidence that they are also reliable. Presented with such records I felt compelled to look at this evidence, analyse the Fatima events and eventually write my own book.2 It is very difficult to distinguish between genuine, reliable witnesses and opportunists who have subsequently learned about the facts and later produced statements based on the “me too” approach. Therefore in my analysis I have excluded statements which surfaced during later investigations of the events. Using the published materials I try to present scientific explanations of the possible techniques applied during these events without involving supernatural forces.